Mental health interventions for adolescents living with HIV/AIDS in sub-Saharan Africa: protocol for a systematic review - Dorothy Serwaa Boakye; Samuel Adjorlolo; Eugenia Xatse; Vincent Valentine Akorli; Paul Kwame Adjorlolo; Yvonne Yawa Battanis; Abigail Bempomaa Frempong; Lydia Kaki Ocansey; Cecillia Yeboah (BMJ Open)
Introduction Adolescents living with HIV/AIDS in sub-Saharan Africa have heightened risk for mental health and psychosocial burden owing to their exposure to a multiplicity of adverse conditions such as stigma and discrimination. However, there is no comprehensive evidence synthesis and evaluation of the effectiveness of mental health interventions for adolescents living with HIV/AIDS in this region. We aim to conduct a systematic review to synthesise the literature on existing mental health interventions for adolescents living with HIV/AIDS in sub-Saharan Africa.Methods and analysis This review will follow the Preferred Reporting Items for Systematic reviews and Meta-Analyses reporting guidelines. Eligible studies will include those investigating the effectiveness of psychosocial, psychological or other forms of interventions on mental health outcomes, conducted in sub-Saharan African countries and involving adolescents (aged 10–19 years) living with HIV/AIDS. Comprehensive searches will be conducted in electronic databases (PubMed, MEDLINE, CINAHL, Scopus and PsycINFO) and grey literature sources. The search will be restricted to studies published from 2004 onwards and in the English language. Study authors will be contacted, and reference lists of retrieved articles will be reviewed for additional papers. Study selection and data extraction will be performed by two independent reviewers, with any disagreements resolved by consensus or involving a third party. A narrative synthesis will be conducted, and if possible, meta-analyses will be performed to estimate the overall effect sizes of interventions on mental health outcomes. Eligible studies will undergo quality assessment using standardised criteria appropriate for each respective study design.Ethics and dissemination No primary data collection will be undertaken; therefore, no ethical approval is required. The findings of this review will be disseminated through publication in a peer-reviewed journal and presented at relevant conferences.PROSPERO registration number CRD42024538975